Intestine-Liver Axis On-Chip Reveals the Intestinal Protective Role on Hepatic Damage by Emulating Ethanol First-Pass Metabolism - De Gregorio, Vincenza; Telesco, Mariarosaria; Corrado, Brunella; Rosiello, Valerio; Urciuolo, Francesco; Netti, Paolo A.; Imparato, Giorgia (Frontiers in Bioengineering and Biotechnology, 2020)
Intestine-Liver-on-chip systems can be useful to predict oral drug administration and first-pass metabolism in vitro in order to partly replacing the animal model. While organ on chip technology can count on sophisticated micro-physiological devices, the engineered organ used still remain artificial surrogates of the native counterparts. Here, we used a bottom-up tissue engineering strategy to build-up physiologically functional 3D Human Intestine Model (3D-HIM) as well as 3D Liver-microtissues (HepG2-mTPs) in vitro and designed a microfluidic Intestine-Liver-On-Chip (InLiver-OC) to emulate first-pass mechanism occurring in vivo. Our results highlight the ethanol-induced 3D-HIM hyper-permeability and stromal injury, the intestinal prevention on the liver injury as well as the synergic contribution of the two 3D tissue models on the release of metabolic enzymes after high amount of ethanol administration.